Diagnóstico das áreas de preservação permanente de um rio transfronteiriço: o caso das margens de um segmento do rio Quaraí/Cuareím - Bervig, Aline Andressa (2015)
Demand for use of natural resources is becoming more intense to meet the basic and vital needs of mankind as well as for its economic exploitation. Aimed at regulating the exploitation of water resources some countries have established standards and environmental protection laws. In situations where natural resources are in the border regions of two or more countries, or in the case of transboundary rivers, the Laws and agreements are essential for the shared management to succeed. Taking as a reference point the river, the existence of Permanent Preservation Areas / ribereños hills (APP's) is essential for the preservation of its banks and consequently the very water resources. The expansion of urban and / or agricultural land space implies the elimination of APP's causing environmental damage. Therefore, this study aimed to analyze the conditions of the Permanent Preservation Areas (PPAs) and ribereños mountains, as are called the APP's Uruguay, on the banks of a segment of the border Rio Quaraí / Cuareim, located on the border between Brazil Uruguay. The qualitative methodology initially a literature review, performed a comparison between forest legislation and Brazilian water resources and environmental laws Uruguayan. Satellite images were used for location and analysis of the studied in Basin Quaraí / Cuareim River, located between the affluent Arroyo Pintado Grande in the east, and the Arroyo Tamandu the West. As a result it was found that there's APP / preserved ribereños hills. Among the irregular use of Permanent Preservation Areas can highlight the extraction of sand from the river banks and the advance of the agricultural frontier, leading the urgent need to mitigate the mentioned environmental problems. Urban sprawl was also a problem in the region. There is the need for greater monitoring and effective enforcement of Uruguayan and Brazilian legislation, as well, there will decrease the degradation of the banks of the Rio Quaraí / Cuareim and the necessary recovery of degraded areas today. Existing Development Joint Committees should seek increasingly shared management in the region as well as to guide the regulation of the aforementioned areas. On the issue of comparison of Brazilian and Uruguayan legislation it revealed that there would be a need to standardize the width of the APP / ribereños hills in Rio segment Quaraí / Cuareim analyzed. If there is an increase in this area, mainly in the Uruguayan margin, preservation will be more effective and environmental quality of the border region will be improved.